Pelatihan Stimulasi dan Deteksi Dini Tumbuh Kembang Anak Usia Dini untuk Guru TK/RA/PAUD: Training on Stimulation and Early Detection of Early Childhood Growth and Development for Kindergarten/RA/PAUD Teachers - Hani Sutianingsih; Darti Rumiatun; Yaneu Nuraineu (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
Stimulation activities for early childhood development can be carried out in school learning activities (TK/RA/PAUD) by teachers by paying attention to several aspects of development that must be achieved by early childhood. The purpose of this community service activity is to increase the knowledge of kindergarten/RA/PAUD teachers in conducting stimulation and early detection of early childhood growth and development as well as socializing activities of stimulation and early detection of early childhood growth and development to the community. The training method is held in a hybrid manner (the theoretical material is provided online while the practicum material is carried out offline). Community outreach activities were divided into three stages of activity, namely pre-intervention, intervention and post-intervention for 15 kindergarten/RA/PAUD teachers in Kaduagung Timur Village, Lebak Regency, Banten. The results of community service activities show an increase in the average knowledge of kindergarten/RA/PAUD teachers regarding stimulation, early detection, and early childhood development of 33.33 (p=0.000), it is proven that this community service activity has a positive impact on teacher knowledge Kindergarten/RA/PAUD regarding stimulation, early detection, and early childhood development. Monitoring and evaluation results show that kindergarten/RA/PAUD teachers have socialized ways of stimulation, early detection, and early childhood development and development to parents, so that the dissemination of information regarding stimulation and early detection of growth and development can be carried out.